Analysis of Efficacy and Safety of Modified Transfrontal Puncture Drainage in Hypertensive Basal Ganglia Hemorrhage Patients - Wang, Wenxin; Lv, Wei; Yang, Jianquan (Frontiers in Surgery, 2022)
Objective The study aimed to explore the efficacy and safety of modified transfrontal puncture drainage in patients with hypertensive basal ganglia hemorrhage. Methods The study enrolled 102 patients with hypertensive basal ganglia hemorrhage who received treatment at our hospital between April 2020 and June 2020. They were divided into a control group (51 cases, burr hole evacuation of intracranial hematoma) and a study group (51 cases, modified transfrontal puncture drainage) using the random number table method. The operative time, hematoma evacuation rate, time to recovery of consciousness, postoperative Glasgow coma scales (GOS), and the length of hospital stay were compared between the two groups. The postoperative recovery of neurological function in the two groups was observed, and activities of daily living at 3 months postoperatively in the two groups were statistically analyzed. The postoperative complications and recurrent bleeding, as well as prognosis in the two groups, were recorded. Results The operative time, hematoma evacuation rate, time to recovery of consciousness, postoperative GOS scores, time to extubation, and the length of hospital stay of the two groups were compared postoperatively, and the difference was statistically significant (p < 0.05). The preoperative neurological function of the two groups was compared, and the difference was statistically insignificant (P > 0.05). The postoperative neurological function of the study group was lower than that of the control group, and the difference was statistically significant (P < 0.05). The postoperative incidence of stress ulcer, renal failure, and recurrent bleeding in the two groups was compared, and the difference was statistically insignificant (p > 0.05). The rate of pulmonary infections and gastrointestinal bleeding in the study group was lower than that of the control group, and the difference was statistically significant (P < 0.05). The mortality rate of the study group was 1.96% (1/51) and that of the control group was 3.92% (2/51), and the difference was statistically insignificant (p > 0.05). The activities of daily living in the two groups were compared and the difference was statistically insignificant (p > 0.05). Conclusion Modified transfrontal puncture drainage can effectively treat hypertensive basal ganglia hemorrhage patients and has relatively good safety.